Genome-Wide Association Mapping in the Global Diversity Set Reveals New QTL Controlling Root System and Related Shoot Variation in Barley - Reinert, Stephan; Kortz, Annika; Léon, Jens; Naz, Ali A. (Frontiers in Plant Science, 2016)
The fibrous root system is a visible sign of ecological adaptation among barley natural populations. In the present study, we utilized rich barley diversity to dissect the genetic basis of root system variation and its link with shoot attributes under well-water and drought conditions. Genome-wide association mapping of phenotype data using a dense genetic map (5892 SNP markers) revealed 17 putative QTL for root and shoot traits. Among these, at 14 loci the preeminence of exotic QTL alleles resulted in trait improvements. The most promising QTL were quantified using haplotype analysis at local and global genome levels. The strongest QTL was found on chromosome 1H which accounted for root dry weight and tiller number simultaneously. Candidate gene analysis across the targeted region detected a crucial amino acid substitution mutation in the conserved domain of a WRKY29 transcription factor among genotypes bearing major and minor QTL alleles. Similarly, the drought inducible QTL QRdw.5H (5H, 95.0 cM) seems to underlie 37 amino acid deletion and substitution mutations in the conserved domain of two related genes CBF10B and CBF10A, respectively. The identification and further characterization of these candidate genes will be essential to decipher genetics behind developmental and natural adaptation mechanisms of barley.